Effect of temperature on the pathogenesis, accumulation of viral and satellite RNAs and on plant proteome in peanut stunt virus and satellite RNA-infected plants - Obrępalska-Stęplowska, Aleksandra; Renaut, Jenny; Planchon, Sebastien; Przybylska, Arnika; Wieczorek, Przemysław; Barylski, Jakub; Palukaitis, Peter (Frontiers in Plant Science, 2015)
Temperature is an important environmental factor influencing plant development in natural and diseased conditions. The growth rate of plants grown at 27°C is more rapid than for plants grown at 21°C. Thus, temperature affects the rate of pathogenesis progression in individual plants. We have analyzed the effect of temperature conditions (either 21°C or 27°C during the day) on the accumulation rate of the virus and satellite RNA (satRNA) in Nicotiana benthamiana plants infected by peanut stunt virus (PSV) with and without its satRNA, at four time points. In addition, we extracted proteins from PSV and PSV+satRNA-infected plants harvested at 21 dpi, when disease symptoms began to appear on plants grown at 21°C and were well developed on those grown at 27°C, to assess the proteome profile in infected plants compared to mock-inoculated plants grown at these two temperatures, using 2D-gel electrophoresis and mass spectrometry approaches. The accumulation rate of the viral RNAs and satRNA was more rapid at 27°C at the beginning of the infection and then rapidly decreased in PSV-infected plants. At 21 dpi, PSV and satRNA accumulation was higher at 21°C and had a tendency to increase further. In all studied plants grown at 27°C, we observed a significant drop in the identified proteins participating in photosynthesis and carbohydrate metabolism at the proteome level, in comparison to plants maintained at 21°C. On the other hand, the proteins involved in protein metabolic processes were all more abundant in plants grown at 27°C. This was especially evident when PSV-infected plants were analyzed, where increase in abundance of proteins involved in protein synthesis, degradation, and folding was revealed. In mock-inoculated and PSV-infected plants we found an increase in abundance of the majority of stress-related differently-regulated proteins and those associated with protein metabolism. In contrast, in PSV+satRNA-infected plants the shift in the temperature barely increased the level of stress-related proteins.